EUS-guided gallbladder drainage: a learning curve modified by technical progress - Tyberg, Amy; Jha, Kopal; Shah, Shawn; Kedia, Prashant; Gaidhane, Monica; Kahaleh, Michel (Endoscopy International Open, 2020)
Introduction Endoscopic ultrasound-guided gallbladder drainage (EUS-GBD) is an efficacious and safe option for patients who cannot undergo cholecystectomy. It is a technically challenging procedure, requiring skills in EUS, and ERCP. The aim of this study was to define the learning curve for EUS-GBD. Patients and methods Consecutive patients undergoing EUS-GBD by a single operator were included from a prospective registry over 5 years. Demographics, procedure information, post-procedure follow-up data, and information on adverse events were collected. Non-linear regression and CUSUM analyses were conducted for the learning curve. Clinical success was defined as resolution of cholecystitis post-procedure. Results Forty-eight patients were included (58 % male, mean age 76 years). Twenty patients (42 %) had malignant cholecystitis. Most patients had lumen-apposing metal stents (LAMS) (15 mm, n = 29, 60 %; 10 mm, n = 8, 7 %). The remaining patients had FCSEMS (n = 9, 19 %) or plastic stents alone (n = 2, 4 %). Clinical success was achieved in 36 (86 %) of patients. Of the remaining 12, 7 were lost to follow-up and 5 had persistent cholecystitis. 9 patients (19 %) had adverse events including bleeding (n = 4), liver abscesses (n = 2), and hypotension. Two patients passed away post-procedure. Median procedure time was 41 minutes (range 16 – 121 min), with the 41-minute time occurring during the 19th procedure. Procedure durations further reduced, with the last 10 procedures being 20 minutes or under (nonlinear regression p value P < 0.0001).Conclusion Endoscopists experienced in EUS-GBD are expected to achieve a reduction in procedure time over successive cases, with efficiency reached at 41 minutes and a learning rate of 19 cases. Continued improvement is demonstrated with additional experience